Staphylococcus aureus costochondritis and chest wall abscess in a COVID-19 patient treated with tocilizumab - ŞANAL TOPRAK, CANAN; ODABAŞI, ZEKAVER (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2021)
Coronavirus disease 2019 (COVID-19) is a worldwide pandemic, causing a global health threat. Up to 15% of the confirmed cases develop severe disease, requiring hospitalization or intensive care unit (ICU) admission. Tocilizumab, an IL-6 receptor antagonist, is a promising treatment of severe pneumonia with acute respiratory distress syndrome (ARDS) or cytokine release syndrome (CRS) in the course of COVID-19. We report a suppurative costochondritis and chest wall abscess in a severe COVID-19 patient treated with tocilizumab.
Keywords: Abscess; chest wall; costochondritis; COVID-19; tocilizumab; SERIOUS INFECTIONS; RISK